Bio-Availability, Anticancer Potential, and Chemical Data of Lycopene: An Overview and Technological Prospecting - Adriany das Graças Nascimento Amorim; Andreanne Gomes Vasconcelos; Jessica Souza; Ana Oliveira; Beatriz Gullón; José Roberto de Souza de Almeida Leite; Manuela Pintado (MDPI AG, 2022)
The purpose of this review was to collect relevant chemical data about lycopene and its isomers, which can be extracted using different non-polar or polar aprotic solvents by SC-CO2 or biosynthesis as a friendly technique. Lycopene and other carotenoids can be identified and quantified by UV-Vis and HPLC using a C18 or C30 column, while their characterization is possible by UV-Vis, Fluorescence, FTIR, MS, NMR, and DSC assays. Among these techniques, the last four can compare lycopene isomers and identify cis or all-trans-lycopene. FTIR, MS, and NMR techniques are more suitable for the verification of the purity of lycopene extracts due to the signal complexity generated for each isomer, which enables identification by subtle differences. Additionally, some biological activities of lycopene isolated from red vegetables have already been confirmed, such as anti-inflammatory, antioxidant, and cytotoxic activity against cancer cells, probably by activating several pathways. The encapsulation of lycopene in nanoparticles demonstrated an improvement in oral delivery, and ex vivo assessments determined that these nanoparticles had better permeation and low cytotoxicity against human cells with enhanced permeation. These data suggest that lycopene has the potential to be applied in the food and pharmaceutical industries, as well as in cosmetic products.